Interesse público: condições necessárias à sua existência - Melo Filho, Oscar Vilaça de (2007)
Today it is sufficiently common to find administrative, legislative and judicial acts that have as bedding (motivation) the public interest. On behalf of the public interest, the government, by means of its instituted powers, has taken decisions that, in the truth, do not find any endorsement in the social will, neither in its interests. But the words are vacant and ambiguous, and besides, there are many indeterminate legal concepts in law. As a good example, we can mention "public interest". Face to the report, judiciary power many times tends to control definitive act, for this to meet friction of "public interest", what it makes to paralyze the legal action, that starts to make believe that data in case will be staining the separation of powers. And, thus, in them we find each time more submitted the acts that, on behalf of the "public interest", come imposing measured that they do not find endorsement in the constitutional model adopted by the Federative Republic of Brazil. Therefore, we can see how much it is difficult to delimit the concept of "public interest", but we decide to trace some necessary conditions to its presence, for that thus, when, stained one of these conditions, let us exclude such situation of the concept of "public interest"